A DISPLAY WEEK LIKE NO OTHER. (19th September 2020) - Atwood, Stephen P.
Abstract: When I heard Display Week 2020 was being turned into an online event, I didn't know what to think. Of course, I had high expectations—anything put together by the Display Week Program Committee and supported by the team at PCM was going to be great. Still, I had never experienced a virtual conference before and had some concerns about how it would all come together. I'm sure I wasn't alone. Thankfully, when the first day came and we all signed in, the results were impressive. The format was intuitive, and the technical quality of the presentations was quite nice. There were some hiccups, as we've all come to expect from this new platform of video conferencing. But foremost, all the great content and events that were promised were there to enjoy.